Families of Animal Rights Activists as a Basis of Support for Ideological Delinquency—A Phenomenological Study - Inbar-Frohlich, Tali (International journal of offender therapy and comparative criminology, 2021)
The presented study examined dynamics and perceptions among family members of ideologues lawbreaking animal rights activists. In the course of the study, parents and spouses of activists were interviewed, and its findings highlighted a number of key themes: glorification of the activist, an envy directed toward elements of the activism; personal gain acquired by virtue of the relationship, as well as self-discovery which family members experienced by their exposure to activism. By using Maruna’s “redemption script” (2001), the study presents the manner by which perception of an activist as an idealist, leads his family members to construct a new narrative that qualifies transgressions based on ideology. The redemption script turns out to be bidirectional. Thus, while Maruna presented it as an aid for desisting delinquency, the study indicates that as far as it concerns breaking the law in favor of animals, it can mobilize family members to support all shades of activism.